Open to the World: Countryman’s Rodeo - Jim Hoy (Symphony in the Flint Hills, 2014)
For many years to residents of Chase, Butler, and Greenwood counties, the Fourth of July and Countryman’s Rodeo were synonymous. Many Flint Hills pasturemen, like the Pinkston brothers of Bazaar, were on horseback in a pasture every day of the week from mid-April until all the steers had been shipped in October every day except for one and that day was the Fourth when they went to Countryman’s Rodeo.
Keywords: rodeo; Countryman’s Rodeo; cattle; cows; bulldogging; bull riding; ribbon roping; wild cow milking; sport; Kansas; ranch; Professional Rodeo Cowboys Association; PRCA; famous